Enhancing Fuel Economy in Heavy-Duty Trucks: A Contemporary Approach - Vimalesan, Vignesh (International Journal of Scientific Research and Management (IJSRM), 2024)
This article reviews the effect of load-based speed control (LBSC) and gear-down protection (GDP) features on fuel consumption in heavy-duty trucks. These two electronic features, developed by Cummins Inc., are major developments in the field of engine management for optimum fuel economy. LBSC controls engine speed based on operating conditions, while GDP encourages operation in top gear for maximum fuel economy. Their mechanisms, benefits, and combined impact on fuel consumption and driver behavior are discussed. The discussion also involves challenges and future developments in this field. Research indicates that LBSC and GDP can offer significant improvements in fuel savings, up to 7% improvement in fuel efficiency. LBSC and GDP contribute to cutting fuel consumption and serve as virtual driver trainers, contributing to more efficient driving behavior. This article concludes that LBSC and GDP are important tools that help fleet managers reduce operation costs and environmental impact within the trucking industry.